PELATIHAN PENGEMBANGAN KEMAMPUAN SENI DENGAN APE BERBASIS BAHAN KERTAS ASTURO BAGI KOMUNITAS PRAKTISI PROGRAM SEKOLAH PENGGERAK WILAYAH SURABAYA 2 - Aisyah Aisyah; Isabella Hasiana; Ervin Nurul Affrida (PeKA: Jurnal Pengabdian Kepada Masyarakat, 2022)
Art skills development training with asturo paper-based APE for the community of practitioners of the driving school program which was attended by five kindergartens in East Surabaya. This activity aims to: (1) participants have skills in making media to develop artistic abilities; (2). Participants have skills in making educational aids made from asturo paper as a medium in learning activities in kindergarten or early childhood. The training methods used include lectures, questions and answers, demonstrations of how to make what is trained and practice making media from asturo paper. The results obtained from this training are that individuals are able to understand and master the concept of art development using asturo paper and have skills in making educational aids from asturo paper as learning media